Dark side or bright side: The impact of alcohol drinking on the trust of Chinese rural residents - Jie Dong; Qiran Zhao; Yanjun Ren (International Journal of Environmental Research and Public Health, 2022)
Existing studies have explored the causal effect of social capital on harmful drinking, while the effect of drinking habits on trust is scant. In China, drinking rituals and drinking culture are considered important ways of promoting social interaction and trust, especially in rural areas where traditional culture is stronger. Based on a field survey in rural China in 2019, this paper explores the relationship between drinking habits and trust. First, we found a negative relationship between drinking habits and trust, indicating that those people who drink alcohol are more likely to have a lower trust. Second, we found significant heterogeneity in the effect of alcohol consumption on social trust across various groups. Specifically, the negative effects of alcohol consumption on trust were stronger for the females than for males; drinking alcohol did not reduce the level of trust among the Chinese Communist Party (CCP) in rural China; compared with the Han nationality, we found that the effect of drinking on trust was not significant for the ethnic minority. Third, we observed that the negative effects of alcohol consumption on trust had thresholds across age and income. Among people under 51, the risk of trust from drinking was greater than for those over 51; the negative effect of drinking on residents' trust was more obvious in low-income families, but not significant in the group with an annual household income of more than CNY 40,000. Our empirical study provides a deeper understanding of drinking culture in rural China from a dialectical perspective.
Keywords: 330; dark side; alcohol drinking; trust